PENDAMPINGAN AKADEMIK: OPTIMALISASI PEMAHAMAN FIKIH EMPAT MADZHAB BAGI MAHASISWA - Mirza Elmy Safira; Muhammad Yusron Maulana El-Yunusi; Ika Faiqotul Himmah (STKIP PGRI SITUBONDO, 2025)
Fiqh is one of the key branches of Islamic legal studies, serving as a guide for Muslims in their daily lives. An understanding of fiqh cannot be separated from the study of the four major schools of thought in Islam, namely the Hanafi, Maliki, Shafi’i and Hanbali schools. However, some students still have a limited understanding of the methodological differences and characteristics of each of these schools of thought. Therefore, academic mentoring is required to strengthen students’ understanding of fiqh and the four schools of thought. This study aims to describe the implementation of mentoring activities for undergraduate students at Sunan Giri University, Surabaya, in understanding fiqh and the four schools of thought. The method employed was a qualitative descriptive approach through academic discussions, textual analysis, and academic mentoring. The results of the activities indicate that this mentoring was effective in enhancing students’ understanding of the basic concepts of fiqh, the historical development of the schools of thought, and the differences in the methods of ijtihad employed by the imams of the schools of thought. These activities also fostered an attitude of tolerance towards differing opinions within Islamic law.